2012
DOI: 10.1002/ccd.24732
|View full text |Cite
|
Sign up to set email alerts
|

Comparable clinical safety and efficacy of biodegradable versus durable polymer paclitaxel eluting stents despite shorter dual antiplatelet therapy: Insights from a multicenter, propensity score‐matched registry

Abstract: In this observational analysis, BP-PES were comparable to DP-PES, with regard to incidence of repeated revascularizations, stent thromboses and MACCE despite earlier DAPT discontinuation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…These novel stents incorporated new thin-strut cobalt-chromium stent platforms, more biocompatible or biodegradable polymer matrices and new rapamycin analogues, like zotarolimus and everolimus, with controllable drug release kinetics. Several clinical studies have shown differences in adverse events among patients receiving different DES platforms [5][6][7] . Although some clinical trials 8 and early preclinical investigations 3,9 have hypothesised the role of paclitaxel in the overall outcome and biological effect, there are limited data studying the independent role of an eluted drug in the overall vascular healing response.…”
Section: Introductionmentioning
confidence: 99%
“…These novel stents incorporated new thin-strut cobalt-chromium stent platforms, more biocompatible or biodegradable polymer matrices and new rapamycin analogues, like zotarolimus and everolimus, with controllable drug release kinetics. Several clinical studies have shown differences in adverse events among patients receiving different DES platforms [5][6][7] . Although some clinical trials 8 and early preclinical investigations 3,9 have hypothesised the role of paclitaxel in the overall outcome and biological effect, there are limited data studying the independent role of an eluted drug in the overall vascular healing response.…”
Section: Introductionmentioning
confidence: 99%
“…BP‐DES have been proposed to allow a shorter duration of DAPT due to improved vascular healing response in the stented segment . In light of this theoretical advantage, BP‐DES might offer a valuable therapeutic option to patients at high risk of bleeding or deemed unsuitable for prolonged used of DAPT, with minimal penalty in terms of safety and efficacy outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…Even though a total number of 12 randomized trials were included in this current analysis, our results were similar with that of the study published by Wang et al [ 21 ] Excluding data that were obtained from randomized trials, even an observational study comparing BP-DES with DP-PES showed comparable adverse outcomes (TVR, MACEs, ST) between these 2 types of stents during a 1-year follow-up period. [ 22 ] The LEADERS trial involving 1707 patients from 10 centers showed BP-DES to be noninferior to SES in terms of the primary endpoints at 5 years; however, BP-DES were associated with a significantly lower rate of very late (from 1 year to 5 years) ST than DP-SES. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%